Complementary modulation of N2 and CRN by conflict frequency. (15th April 2014) - Grützmann, Rosa; Riesel, Anja; Klawohn, Julia; Kathmann, Norbert; Endrass, Tanja
Abstract The present study investigated the modulation of the N2 and the correct‐related negativity (CRN) by conflict frequency. Conflict costs, as measured by reaction times and error rate, were reduced with increasing conflict frequency, indicating improved conflict resolution. N2 amplitudes in incompatible trials increased with higher conflict frequency, while postresponse CRN amplitudes decreased. In concert with behavioral findings of reduced conflict costs and greater interference suppression, the increase of N2 might reflect enhanced conflict resolution during stimulus processing. The CRN, however, might reflect postresponse implementation of cognitive control, which is reduced when conflict is already adequately resolved during stimulus processing. Furthermore, N2 and CRN in incompatible trials were inversely related on the between‐ and within‐subject level, implying that the two modes of implementing cognitive control are applied complementarily.